(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2019)
The soil cover structure and biomass characteristics of the phytocenoses in ArcelorMittal Kriviy Rih waste dump were studied. Soil cover structure and soil contour parameters were detailed using 3D-modelling. The use of the 3D-modelling is more objectively in contrast of mapping for industrial landscapes characterization. It confirms by increasing of object area by 50%. The waste dump area, according to the map is 38 ha, account for, and it is 55 ha according to 3D-model, the correction factor is 1.44. Confirmed, that 3D-modelling is necessary to predict the industrial objects self-recovery intensification and dynamics. It also useful to assess the quality of fertile and potentially fertile soils applying to waste dump survey. Structure of soil cover at waste dump is represented by combinations of primitive soils which have different genesis and depth with rocky substrates. More developed soils are situated on clay substrates. Phytocenoses with domination of Koeleria cristata, Achilea nobilis and Lathyrus tuberosus are adapted to survive and distribute on waste dumps with clay cover. Plant communities with Securigera varia, Hieracium echioides and Poa angustifolia domination are adapted to the stone substrates. Phytocenoses with Koeleria cristata domination are forming the biggest biomass (103.4 g/m2) on clays. The most biomass formed in Securigera varia phytocenoses – 20,9 g/m2 on the stone substrates. The average biomass of the grass phytocenoses on waste dumps for clay soils are 21.8 g/m2, and for stone substrates are 6.9 g/m2.